The role of Folksonmies in organizing and retrieving information on the web: An analytical study (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present study aims to introduce the most important tools of digital organization in the web environment, which correspond to the wishes of the developers and the modernization of sites in improving the access to information by the beneficiaries, especially after developments in the web environment 2،0, which contributed significantly to the existence of quantum And the lack of control over the traditional methods and tools. The study concluded with a set of results, the most important of which was that Folksonmies added a new dimension to the organization of information on the web. Here is the process of organizing information based on folksonomis need the human element more than the search engines programs. The study included several basic axes that spoke about the methodology, its concept and types. The talk about the Taxonomy and its understanding and its advantages were explained. The Folksonmies (its Arabicization and its concept), its types and applications, and the presentation of the most prominent Arab sites that use Folksonmies in the organization of their contents were finally explained. These tools were compared and what is the difference between ontology Detail and identify points of difference between them.